Do Service Quality, Price, and Comfort Affect Consumer Satisfaction: The Study of Ride-Hailing Services in Malaysia - Zulkiffli, Wan Farha Wan; Hashim, Nik Alif Amri Nik; Mahshar, Munirah; Simpong, Derweanna Bah; Anuar, Nur Izzati Mohamad; Muhammad, Mohd Zulkifli; Yusoff, Nur Dalila Mat (The journal of contemporary issues in business and government, 2021)
The purpose of this study is to examine how service quality, price, and comfort affect consumer satisfaction towards ride-hailing services in Malaysia. In view of several ride- hailing service issues such as frequent booking cancellation by the drivers and increased scheduled price due to the unavailability of drivers, the consumers have, in turn, expressed a low level of satisfaction towards ride-hailing services in Malaysia. Hence, this study employed a quantitative technique to identify the associations between service quality, price, and comfort with consumer satisfaction towards ride-hailing services in Malaysia by distributing 250 questionnaires to the younger generation of age 18-35 years old in Klang Valley. All research hypotheses were accepted, thus affirming service quality, price, and comfort as the main factors influencing consumer satisfaction.